Comparison of feed additives in rations for growing-finishing swine - Koch, B.A.; Loeppke, D.W. (Kansas Agricultural Experiment Station, 2011)
Seventy-two pigs were used. They averaged about 50 pounds each at the start of the experiment. During the first 28 days the pigs that received a diet containing Aureo S.P.-250 (100 gms. Chlortetracycline, 100 gms. Sulfamethazine and 50 gms. Penicillin per ton of feed) gained about 13% faster than pigs on diets containing either chloreteracycline or tylosin at 10 gms. Per ton of feed
Keywords: Swine; Feed additives; Chlortetracycline; Performance